PWE-183 Preliminary Significant Findings From A Randomised Control Trial Of Posterior Tibial Nerve Stimulation In Systemic Sclerosis Associated Faecal Incontinence. (9th June 2014) - Butt, SK; Alam, A; Raeburn, A; Liwanag, J; Ong, VH; Denton, CP; Murray, CD; Zarate-Lopez, N; Emmanuel, A
Abstract : Introduction: The gastrointestinal tract is affected in up to 90% of Systemic Sclerosis (SSc) patients with faecal incontinence (FI) being reported in up to 38%. Passive faecal incontinence secondary to internal anal sphincter atrophy is the characteristic finding. We have shown that neuropathic changes are implicated in SSc patients with FI and sacral nerve stimulation has emerged as a potentially beneficial therapy in SSc. However this is expensive, invasive, not widely available and we have shown that medium term efficacy is poor. Posterior tibial nerve stimulation (PTNS) is a potential alternative to modulate the sacral plexus indirectly, with none of these disadvantages. This is the preliminary data on a randomised placebo controlled trial of PTNS versus sham PTNS to determine if nerve modulation is an effective treatment in SSc associated FI. Methods: We commenced a prospective randomised single-blind study of SSc patients with FI in February 2013 from a specialist Scleroderma unit. Baseline symptom scoring (bowel diary, Wexner), manometry and endoanal ultrasound were completed prior to randomization to PTNS or sham. PTNS was administered conventionally, by insertion of an acupuncture needle according to anatomical landmarks, connected to an electrical stimulator. Sham PTNS was administered in identical fashion but the PTNS surface electrode was not connected and instead separate TENS surface electrodes were connected to a TENS unit. Each patient underwent blinded intervention for 30 min periods, once a week for 12 weeks. The primary endpoints were the percentage reduction in faecal incontinence episodes and change in Wexner incontinence scores. Results: A total of 13 SSc patients (11 f), mean age 61 (36–72) completed the trial by October 2013. Of these 6 (5 f) underwent PTNS and 7 (6 f) patients underwent sham stimulation. All PTNS patients showed a reduction (5–100%) in the number of FI episodes in comparison to 0 sham patients at 12 weeks (p < 0.01 (CI: -81.49–14.34)). This matched an improvement in mean Wexner scores from baseline to treatment end (14.8 to 10.8 vs 13.4 to 13.6, true vs sham respectively, p = 0.03. Conclusion: This pilot data is demonstrating significant effects of PTNS in Scleroderma-associated FI. We present this significant initial data but anticipate having at least 25 completed patients by May 2014. Disclosure of Interest: None Declared.